Influential factors of impulsive buying through electronic payment card among working individuals / Muhamad Azrul A Zahari - A Zahari, Muhamad Azrul (2013)
The purpose of this research is to determine the factors which could influence working individuals towards impulsive buying through electronic payment card. The sample comprised 100 of working individuals who works in the Alor Setar were collected by using simple random sampling. This study embraces three independent variables has been adapted which is convenience, sales promotion and mode of payment, meanwhile the dependent variable is impulsive buying through electronic payment card. In order to determine the relationship between those variables, this study has used reliability analysis, descriptive analysis, Pearson correlation analysis and regression analysis which comprised of analysis of variance (ANOVA), coefficients determinations, multiple regression analysis and hypothesis testing. The results of the findings state that impulsive buying through electronic payment card has a relationship between all variables factors which is convenience, sales promotion and mode of payment